If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -60 = -6(-8x + 2) Reorder the terms: -60 = -6(2 + -8x) -60 = (2 * -6 + -8x * -6) -60 = (-12 + 48x) Solving -60 = -12 + 48x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-48x' to each side of the equation. -60 + -48x = -12 + 48x + -48x Combine like terms: 48x + -48x = 0 -60 + -48x = -12 + 0 -60 + -48x = -12 Add '60' to each side of the equation. -60 + 60 + -48x = -12 + 60 Combine like terms: -60 + 60 = 0 0 + -48x = -12 + 60 -48x = -12 + 60 Combine like terms: -12 + 60 = 48 -48x = 48 Divide each side by '-48'. x = -1 Simplifying x = -1
| 4r^2-23r-6=0 | | 4(6)-y=7 | | x+2+3x-4=15 | | -0.08x=0.56 | | 3x+9=6x+2 | | 8.75+1.25=15.00 | | 6k^2-2k=0 | | 2t=2(t+5) | | 8.75-1.25=15.00 | | X+29+5x-3-4X=X+44 | | Lnx+ln(x+2)=3 | | 5x+2y=-2 | | -2(3b-4)+6(1+2b)=-4 | | 3(1+8x)+7x=65 | | 4m+12=8 | | 7(1+8n)+7(n+6)=49 | | -4x=x-(4x) | | 3y-1+2y=9 | | 16+w*10=-154 | | x^2+25=49 | | 5b*4=30*12 | | -84=-6(p+7) | | -5(p+2)=2(2p-15) | | 3x-9=15-5x | | graphx+y=4 | | 2a+18+26=4a+2 | | -14=n-2-7n | | -24=-4(n-2) | | -3x=3x+12 | | 7a-2=-9+7a | | 12y^2-20y+8=0 | | 4x-2x-5=7 |